Improving mechanical properties of novel flax/tannin composites through different chemical treatments - Zhu, Jinchun; Zhu, Huijun; Immonen, K.; Brighton, James; Abhyankar, Hrushikesh (Elsevier, 2015)
Due to the inherent environmental benefits of using renewable materials, mimosa tannin resin (a natural phenolic resin) reinforced by flax fibres could offer desirable characteristics (lightweight, economic and low environmental impact) aiming at reducing carbon footprint of superlight electric vehicles. The non-woven flax mats were chemically treated (alkali, acetylation, silane and enzymatic treatment) to prepare tannin composites through compression moulding (130 °C/35 min/1.5 MPa). The change in fibre morphology was seen in SEM (scanning electronic microscope) images. The treatments (except enzymatic) showed significant improvement in tensile properties, along with enhancement (acetylation) in flexural properties, but little effect on impact resistance for all treatments. APS (aminopropyl triethoxy siloxane) treated composites showed highest tensile strength of 60 MPa and modulus of 7.5 GPa. BTCA (butanetetracarboxylic acid) treatment led to the highest flexural strength of up to 70 MPa. NaOH treatment retained the impact failure force of about 0.5 kN and sustained the saturation energy (4.86 J) compared to untreated composites (4.80 J).
Keywords: Flax Bio-composites; Tannin; Mechanical performances and surface treatments